Analisis hubungan pengetahuan dan dukungan keluarga dengan kejadian stunting: A literature review - Harno, Harno; Ardian, Iwan; Setyowati, Wahyu Endang; Luthfa, Iskim (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Stunting is a chronic nutritional problem that impacts children's physical growth and cognitive development and contributes to increased long-term morbidity and mortality. Determinants such as parental knowledge, especially maternal knowledge, and family support play a crucial role in stunting prevention. Purpose: To analyze the relationship between knowledge and family support levels and stunting incidence. Method: This study employed a literature review design approach using searchable databases including Scopus, PubMed, EBSCO, and Science Direct. The search was conducted in May 2025. Article inclusion criteria included articles published between 2019 and 2025 that discussed the relationship between knowledge and family support and stunting incidence, in both English and Indonesian. The search terms used were